Targeted Nanoprobes Reveal Early Time Point Kinetics In Vivo by Time-Resolved MRI - Bhirde, Ashwinkumar (Ivyspring International Publisher, 2011)
This commentary highlights the findings by Kessinger et al. (Theranostics 2011; 1: 263-275) that dynamic T2*-weighted magnetic resonance imaging (MRI) of cyclic RGD peptide-encoded superparamagnetic polymeric micelle (SPPM) nanoparticles allows quantitative analysis of tumor integrin αvβ3 expression, which can exclude the effect of blood volume and extravascular signal components and thus provide less biased tumor contrast and receptor specificity of probes.